(untitled) (Książnica Śląska, 2025)
Ernest Farnik was a theatre lover, for years, he cooperated with the Society of Friends of the Polish Theatre in Katowice, served on several committees assessing plays for people’s theatres, was a viewer of numerous performances, as well as the owner of a large collection of theatrical items. The author of the article analyses the reviews of Ernest Farnik from the theatre season 1933/1934, recorded on copies of theatre programme brochures from his legacy and compares them with theatrical reviews published in the press (“Polska Zachodnia”, “Polonia”, “Górnoślązak”, “Goniec Śląski”). Simultaneously, she delves into the state of the theatrical scene at that time, describes the alterations taking place within the theatre, and recalls individuals associated with the then theatre and artistic life in Upper Silesia.